Quantity discrimination, decision-making, and the role of early-life conditions in a lizard - Pablo Recio; Dalton C. Leibold; Ondi L. Crino; Christopher R. Friesen; Amelia Y. Peardon; Daniel W. A. Noble (Evolutionary Ecology, 2026)
Quantity discrimination affects a range of behaviours essential for fitness, including social interactions, navigation, and foraging and is widespread across animal taxa. However, in reptiles, evidence for this ability — particularly for small number contrasts — remains limited and mixed. Early-life conditions, such as hormonal exposure and temperature, can also shape brain development and cognitive performance, potentially affecting numerical abilities. Here, we tested the ability of the common garden skink ( Lampropholis guichenoti ) to discriminate between quantities and the effects of elevated prenatal glucocorticoids and incubation temperature on quantity discrimination and decision-making. We assessed quantity discrimination using a spontaneous choice test with food as a stimulus. We subjected lizards to five two-choice tests differing in the number of items (1 VS 4, 1 VS 3, 2 VS 4, 2 VS 3, 3 VS 4) while controlling for total length and area. Contrary to our predictions, lizards did not show clear preferences toward the larger items, providing no evidence of spontaneous quantity discrimination in L. guichenoti . Furthermore, prenatal conditions did not influence latency to make a choice, also a proxy for decision-making. Despite these results, further investigation of quantity discrimination in live-prey-feeding reptiles and the impact of early conditions on other taxa remains an important area of research.

Early environmental conditions do not impact behavioural flexibility in an invasive and noninvasive lizard species - Pablo Recio; Dalton C. Leibold; Ondi L. Crino; Kristoffer H. Wild; Christopher R. Friesen; Basile Mauclaire; Amelia Y. Peardon; Daniel W.A. Noble (Animal Behaviour, 2025)

Revisiting the mercury cycle in marine sediments: A potential multifaceted role for Desulfobacterota - Blanca Rincón-Tomás; Anders Lanzén; Pablo Sánchez; Mónica Estupiñán; Isabel Sanz-Sáez; M. Elisabete Bilbao; Diana Rojo; Iñaki Mendibil; Carla Pérez-Cruz; Marta Ferri; Eric Capo; Ion L. Abad-Recio; et al. (Journal of Hazardous Materials, 2024)

A multi-centre peptidomics investigation of food digesta: current state of the art in mass spectrometry analysis and data visualisation - Reto Portmann; Pablo Jiménez-Barrios; Julien Jardin; Lychou Abbühl; Daniela Barile; Marianne Danielsen; Yu-Ping Huang; Trine Kastrup Dalsgaard; Beatriz Miralles; Valérie Briard-Bion; Stefano Cattaneo; Christophe Chambon; et al. (Food Research International, 2023)

Conspecific scent marks may influence underground site selection by a fossorial reptile - Pablo Recio; Gonzalo Rodríguez-Ruiz; Marco Sannolo; José Javier Cuervo; Pilar López; José Martín (Behavioral Ecology and Sociobiology, 2023)
Conspecific cues often provide social information on habitat quality that is considered when deciding to settle at a specific site. The type of sensory cues useful for this will depend on the environment. For amphisbaenians, reptiles adapted to an underground life with highly reduced sight, chemoreception is especially useful to recognize conspecifics. Here, we first analyzed the lipophilic compounds from precloacal gland secretions of the amphisbaenian Blanus cinereus , showing that there were sex- and size-related variations in the proportions of the three major compounds. Then, we tested in the laboratory whether there was an underground site selection based on conspecific chemical cues (substrate scent marks) in two different contexts. In loose substrates, both male and female amphisbaenians tended to choose first the scent-marked substrates more often when the individual that produced the scent, independently of its sex, was relatively larger than the focal individual. In contrast, inside semi-permanent galleries, males, but not females, chose the scent-marked gallery more often when the scent donor, independently of its sex, was relatively smaller. These results suggest that the proportions of compounds in scent marks may allow amphisbaenians to estimate the body size of the producer and that this information affects their site selection decisions. However, the different substrate-dependent responses suggest a different meaning and usefulness of scent marks depending on the context. Significance statement The presence of your conspecific in a site may indicate that this is a “quality” site to live in. If you are blind and live underground, smell is one of the best options for detecting conspecifics and assessing how good are your surroundings. Here, we test whether a blind amphisbaenian reptile that spends its life buried in sandy substrates uses conspecific chemical stimuli to choose where to settle. We found that this decision is influenced by the microhabitat type, sex, and the size difference between the individual that sniffs and the producer of the scent. Amphisbaenians seem to detect and assess conspecific traits based on the differences in compounds in their odors. Therefore, using conspecific scent to assess habitat quality may help fossorial animals to live underground.

Prey quantity discrimination and social experience affect foraging decisions of rock lizards - Pablo Recio; Gonzalo Rodríguez-Ruiz; Pilar López; José Martín (Behavioral Ecology and Sociobiology, 2021)

Transcription and weak expression of HLA-DRB6 : a gene with anomalies in exon 1 and other regions. - Victor M. Fernandez-Soria; Pablo Morales; Maria J. Castro; Belen Suarez; Maria J. Recio; Miguel A. Moreno; Estela Paz-Artal; A. Arnaiz-Villena (Immunogenetics, 1998)

Primate Mhc-E and -G alleles - Antonio Arnaiz-Villena; Jorge Martinez-Laso; Miguel Alvarez; Maria J. Castro; Pilar Varela; Eduardo Gomez-Casado; Belen Suarez; María José Recio; Gilberto Vargas-Alarcón; Pablo Morales (Immunogenetics, 1998)

Primate Mhc-E and -G alleles - A. Arnaiz-Villena; J. Martinez-Laso; Miguel Alvarez; Maria J. Castro; Pilar Varela; Eduardo Gomez-Casado; Belen Suarez; María José Recio; Gilberto Vargas-Alarcón; Pablo Morales (Immunogenetics, 1997)